2015
DOI: 10.1016/j.trsl.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Marked protection against acute renal and hepatic injury after nitrited myoglobin + tin protoporphyrin administration

Abstract: The phenomenon of so called renal “ischemic preconditioning”, whereby an initial ischemic insult induces resistance against subsequent kidney damage, has been well established in the experimental literature. However, a clinically applicable way to safely recapitulate this state has not been defined. We hypothesized that a unique combination of agents (nitrited myoglobin + Sn protoporphyrin) can achieve these ends by safely, and synergistically, increasing cytoprotective proteins (e.g., HO-1, IL-10, haptoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Indeed, a plethora of experimental data support the concept that such redox sensitive ‘stress proteins’ can exert dramatic renal protective effects (reviewed in ref. 8, 9). However, the most effective and safest way(s) of inducing these proteins in kidney remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, a plethora of experimental data support the concept that such redox sensitive ‘stress proteins’ can exert dramatic renal protective effects (reviewed in ref. 8, 9). However, the most effective and safest way(s) of inducing these proteins in kidney remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that administration of a sub-toxic dose of nitrited myoglobin (NMgb), in combination with Sn protoporphyrin, can safely and synergistically up-regulate potent cytoprotective proteins (e.g., HO-1, haptoglobin, IL-10) in mouse kidney (8). Thus, by 18 hrs post agent administration, striking protection against both ischemia-reperfusion and toxic (maleate, glycerol) ARF was induced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These investigators have previously shown that administration of nitrated myoglobin (heme protein) in combination with tin-protoporphyrin (HO-1 inducer) renders striking protection against AKI. 9 In the current study, Zager et al 8 replaced nitrated myoglobin with iron sucrose and showed that preadministration of iron sucrose combined with either tinprotoporphyrin or cyanocobalamin (also a protoporphyrin) induces renal protection in diverse models of AKI, whereas iron-sucrose alone was not effective. Furthermore, remote cardiac injury as measured by plasma troponin I levels was ameliorated.…”
mentioning
confidence: 64%